2021
DOI: 10.1088/1741-2552/ac00d3
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation using electroosmosis

Abstract: Objective. Our laboratory has proposed chemical stimulation of retinal neurons using exogenous glutamate as a biomimetic strategy for treating vision loss caused by photoreceptor (PR) degenerative diseases. Although our previous in-vitro studies using pneumatic actuation indicate that chemical retinal stimulation is achievable, an actuation technology that is amenable to microfabrication, as needed for an in-vivo implantable device, has yet to be realized. In this study, we sought to evaluate electroosmotic fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…While most demonstrations of glutamate activation of retinal ganglion cells from the epiretinal ( Finlayson and Iezzi, 2010 ; Inayat et al, 2015 ) or from the subretinal side ( Rountree et al, 2016 , 2018 , 2020 ) have relied on pneumatic injection ( Rountree et al, 2017b ), it was recognized by Peterman et al (2004) that electroosmotic flow might be better suited as a neurotransmitter release mechanism in a microfabricated device. Kare et al (2021) have shown recently that electroosmosis can be used effectively to dispense glutamate to rat retinas and evoke responses from its ganglion cells with properties similar to those evoked through pneumatic actuation.…”
Section: Components Of a Chemical Retinal Prosthesismentioning
confidence: 99%
“…While most demonstrations of glutamate activation of retinal ganglion cells from the epiretinal ( Finlayson and Iezzi, 2010 ; Inayat et al, 2015 ) or from the subretinal side ( Rountree et al, 2016 , 2018 , 2020 ) have relied on pneumatic injection ( Rountree et al, 2017b ), it was recognized by Peterman et al (2004) that electroosmotic flow might be better suited as a neurotransmitter release mechanism in a microfabricated device. Kare et al (2021) have shown recently that electroosmosis can be used effectively to dispense glutamate to rat retinas and evoke responses from its ganglion cells with properties similar to those evoked through pneumatic actuation.…”
Section: Components Of a Chemical Retinal Prosthesismentioning
confidence: 99%
“…EOF is the convective movement of solvent generated by the preferential electrophoretic movement of mobile counter cations (or anions) through negatively (or positively) charged microchannels, such as glass capillaries, [19,20] nanotubule membranes [21,22] and porous oxide materials. [23,24] Therefore, EOF can even transport solute chemicals in the opposite direction of their electrophoresis [20,25] (Figure S1, Supporting Information). In addition to the charged microchannels, hydrogels are also attractive materials for generating EOF when they possess fixed charges along with their soft and hydrophilic nature.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of external current flow is a unique property of the developed system; many conventional electroosmotic pumps have an external electrode, and therefore chemical delivery with such a system might be accompanied by unwanted electrical stimulation of target cells and tissues. A few previous works of EOF pump [23,24] prevented the current from flowing to outside by utilizing a porous material sandwiched between electrodes; however, in this structure, one of the electrodes is close to the target, which raises concerns about the effects of electrolysis. On the other hand, the electrodes of the present system can be placed away from the delivery target.…”
Section: Introductionmentioning
confidence: 99%
“…Since EOF velocity and pressure are controlled by the applied voltage, EOF provides a wide range of tunability with high resolution. Response latency between voltage application and observable fluid flow is on the order of a few milliseconds . EOF micropumps can be very thin, making them suitable for applications such as lab-on-a-chip and drug delivery devices.…”
Section: Introductionmentioning
confidence: 99%
“…Response latency between voltage application and observable fluid flow is on the order of a few milliseconds. 6 EOF micropumps can be very thin, 7−11 making them suitable for applications such as lab-on-achip and drug delivery devices. These applications demand precise quantification of the relationship between the applied voltage and flow rate and/or pressure.…”
Section: ■ Introductionmentioning
confidence: 99%